International Data Access Network (IDAN) - Silberman, Roxane; Mueller, Dana; Lichtwardt, Beate (International Journal of Population Data Science, 2018)
With legal frameworks changing, administrative data can increasingly be utilised both for official statistics and to facilitate new research, enabling the development of evidence-based policy for the public benefit. Secure access conditions generally apply to using these rich, highly detailed data. However, using data from various sources is difficult when they are fragmented in “silos” between several Research Data Centres (RDCs) as can happen at a national level, and is very likely to be the case at an international level. This is a major obstacle for international comparative research. Based on user consultations, on discussions with international organisations such as OECD and Eurostat and based on lessons learned from projects as, “Data without Boundaries” and the “Nordic Microdata Access Network”, IDAN aims to create a concrete operational international framework enabling access to controlled data for research. IDAN, founded in 2018, involves six RDCs from France, Germany, the Netherlands and the United Kingdom. Initially, the partners’ access systems are being implemented in each partners' premise based on bilateral agreements. This process involves combining requirements of security and surveillance for Safe Rooms, thus paving the way for next steps toward an integrated RDCs network. This presentation will describe how IDAN is setting up a new concrete environment for researchers to work remotely with data from the other partners within their local RDC. The paper will present first project developments, lessons and impact for research that are also of interest for national contexts where administrative data are held in multiple data centres.